Characterization of rabbit antibodies for immunochemical detection of Yersinia enterocolitica - Hochel, I; Skvor, J (Folia microbiologica, 2007)
Rabbit IgG raised against whole cells of Yersinia enterocolitica O:3, O:9 and against a group of pathogenic Y. enterocolitica strains (serotypes O:3, O:5,27, O:8. and O:9) were prepared. The antibody limiting titers were within the range of 1:9.5 x 10(4)-1:7.5 x 10(5). The immunoblotting analysis of Yersinia lipopolysacchides separated by SDS-PAGE showed that IgG against the single serotype O:3 interacted with high-molar-mass LPS of O:3 whereas other antibodies were bound to low-molar-mass LPS of serotypes O:3, O:5,27, O:9 and strain Y. enterocolitica (CNCTC Y 2/68). IgG against the group of pathogenic serotypes also weakly interacted with low-molar-mass LPS of serotypes O:5, O:6,30, and O:10. The cross-reactivity of the antibodies with Y. pseudotuberculosis Ia and/or Y. rohdei b, d, e, f, i, which was observed by means of dot-blotting procedure using the whole bacterial cells as an antigen, was shown not to be caused by LPS of these bacteria. The prepared antibodies were used in the development of indirect competitive ELISA. At the optimum concentration of the immunoreactants the detection limits were within the range of 3-7 x 10(6) colony-forming units per mL.
Keywords: protilátky bakteriální; specificita protilátek; imunoglobulin G; imunologické techniky; Immunologic Techniques; zkřížené reakce; imunoblotting; Lipopolysaccharides; antigeny bakteriální; Cross Reactions; Antigens, Bacterial; antisérum; endopeptidasa K; Immunoglobulin G; Yersinia enterocolitica; Immunoblotting; ELISA; barvení stříbrem; zvířata; Immunization; králíci; Antibodies, Bacterial; lipopolysacharidy; Endopeptidase K; Rabbits; Silver Staining; Immune Sera; Antibody Specificity; Enzyme-Linked Immunosorbent Assay; imunizace; Yersinia; Animals